Helm Pendeteksi Kantuk Untuk Keselamatan Berkendara Menggunakan Sensor Infrared - Herlambang Saputra; Arsia Rini; Siti Hanifah (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2026)
Traffic accidents caused by drowsy drivers are one of the main causes of high accident rates on the road. To help reduce this risk, a drowsiness detection helmet based on infrared sensors has been developed. This device is designed to detect the condition of the driver's eyes using infrared sensors installed inside the helmet. When the eyes are detected to be closed for more than one second, the system interprets this as a sign of drowsiness and issues a warning in the form of a buzzer sound and vibration through a coin vibration motor. The system is controlled by an ESP32 microcontroller, which reads, processes data from the sensors, and activates the warning. Testing was conducted by observing the system's response to open and closed eye conditions. The results show that the device functions as expected, with the warning active when the eyes are closed and deactivated when the eyes are open. All components can be installed in the helmet without compromising comfort or its function as head protection. This device is expected to serve as a practical and effective solution to enhance driving safety, particularly for drivers who frequently travel in fatigued or drowsy conditions. Keywords:Helmet, Sleepiness, Infrared Sensor, ESP32, Riding Safety